2006
DOI: 10.1007/s10495-006-9148-2
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of Fas/Fas ligand/caspase 8 and membrane type 1-matrix metalloproteinase in atretic follicles within dehydroepiandrosterone-induced polycystic ovaries in rats

Abstract: One of the characteristics of polycystic ovary syndrome (PCOS) is the presence of cystic follicles in various stages of growth and atresia, the latter of which is known to be the result of apoptosis and tissue remodeling. To further investigate the process of follicular atresia, we compared ovarian expression and localization of Fas, Fas ligand (FasL), casapse-8 and membrane-type1 matrix metalloproteinase (MT1-MMP) in rats treated with dehydroepiandrosterone (DHEA) as a model of PCOS, and in control rats. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…In humans, the two primary pathways to initiate apoptosis are the death receptor pathway and the mitochondrial pathway [86]. The death receptor pathway is primarily regulated by FasL and caspase 8 in rats [87], and the inhibition of FasL can decrease caspase 8 activity in Jurkat T lymphocytes [88]. In our study, compared with low or high levels of protein, at an optimal level of dietary protein, the mRNA level of FasL was down-regulated in the gills of grass carp.…”
Section: Optimal Level Of Dietary Protein Inhibited Apoptosis Partly mentioning
confidence: 99%
“…In humans, the two primary pathways to initiate apoptosis are the death receptor pathway and the mitochondrial pathway [86]. The death receptor pathway is primarily regulated by FasL and caspase 8 in rats [87], and the inhibition of FasL can decrease caspase 8 activity in Jurkat T lymphocytes [88]. In our study, compared with low or high levels of protein, at an optimal level of dietary protein, the mRNA level of FasL was down-regulated in the gills of grass carp.…”
Section: Optimal Level Of Dietary Protein Inhibited Apoptosis Partly mentioning
confidence: 99%
“…FasL and Fas has also been considered to participate in apoptosis during follicular atresia in the mammalian ovary, based on their expression in ovarian follicles [27,[33][34][35][36][37][38][39][40][41][42] and pro-apoptotic activities of FasL and antibodies to Fas in follicular cells. Increases in the expression of either or both of Fas and FasL have been observed during follicular atresia in mice [36], rats [37,42], cattle [43] and pigs [27].…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the expression of either or both of Fas and FasL have been observed during follicular atresia in mice [36], rats [37,42], cattle [43] and pigs [27]. It has been reported that FasL was expressed in porcine granulosa cells and that its expression level and the percentage of apoptotic cells were increased by the effect of haem oxygenase, whose expression was increased in atretic follicles [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several evidences are documented previously, suggesting that abnormal follicular physiology in PCO may be resulted due to disrupted ovarian tissue remodeling machinery. For instance, PCO is associated with irregular folliculogenesis and extracellular matrix (ECM) modifications along with up-regulation/hyperactivation of MMPs [MMP9 (matrix metalloproteinase-9), MMP2 (matrix metalloproteinase-2) and MT1-MMP (Membrane type 1-matrix metalloproteinase)] [3][4][5] that normally facilitate the degradation of basal lamina to breach the apical ovarian surface epithelium during ovulation. Moreover, normal follicles show HA (hyaluronan) and hyaluronan binding proteins [called as ''hyaladherins'' e.g., TSG-6 (TNF-a-stimulated gene/protein 6), PTX-3 (Pentraxin-3)] coordinated COC (cumulus-oocyte complex) expansion before successful ovulation [6,7], which is missing in PCO.…”
Section: Introductionmentioning
confidence: 99%